Marketing Integrity, Marketing Mix And SWOT Analysis MSME Java Art Souvenir At Kota Tua - Swantari, Anita; Kusumaningrum, Anisa Putri; Gunasuara, Harry Agung; Sandra, Dwi Aprilia; Remilenita, Selvy (CV ODIS, 2023)
This study discusses the marketing strategies of Java Art Souvenir, an MSME in Jakarta Old Town known for its cultural heritage. The research employs a qualitative approach, focusing on the marketing mix (Product, Price, Place, Promotion) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to understand the business dynamics. Java Art Souvenir, owned by Aldy Sanjaya, produces a variety of cultural souvenirs. The study highlights challenges in integrated marketing, particularly in coordinating communication channels. Recommendations include diversifying products, competitive pricing, leveraging the strategic location, and participating in cultural events. SWOT analysis reveals internal strengths in experienced HR and high-quality products, but weaknesses in digital presence and decreased business activity. Opportunities lie in online expansion and partnerships with local art institutions. Strategic recommendations involve creative product development, establishing partnerships, online visibility, and participation in digital marketing trends. In conclusion, addressing weaknesses and capitalizing on opportunities can enhance Java Art Souvenir's position in the dynamic Jakarta Old Town souvenir market.